Epithelial rests of Malassez: from latent cells to active participation in orthodontic movement - Bianca Silva e Silva; Nathalia Carolina Fernandes Fagundes; Bárbara Catarina Lima Nogueira; José Valladares Neto; David Normando; Rafael Rodrigues Lima
ABSTRACT Introduction: The epithelial rests of Malassez (ERM) represent a group of cells in the periodontal ligament classically consisting of latent or quiescent structures associated with pathological processes. However, recent evidence shows that these structures cannot be considered only as cellular debris. The ERM is a major tissue structure, with functions in maintaining the homeostasis of periodontal tissue, including the maintenance of orthodontic movement. Objective: The present literature review aims at presenting the potential functions of ERM, with emphasis on orthodontic movement and the functional structure of the periodontium. Conclusion: ERM cells have a functional activity in modulation of orthodontic movement, trough their potential for differentiation, maintenance functions and the capacity of repairing periodontium.